2019
DOI: 10.1101/769059
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The ATG5 Interactome Links Clathrin Vesicular Trafficking With The ATG8 Lipidation Machinery For Autophagosome Assembly

Abstract: Autophagosome formation involves the sequential actions of conserved ATG family proteins that regulate the lipidation of the ubiquitin-like modifier ATG8 at the nascent isolation membrane.Although the molecular steps driving this process are well understood, the source of membranes supplied for the expanding autophagosome and their mode of delivery remain uncertain. Here, we have used quantitative SILAC-based proteomics to identify proteins that associate with the ATG12~ATG5 conjugate that is crucial for ATG8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 82 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…This interaction was proposed to be mediated by AIM/LIR and stimulate Atg8 conjugation. On the other hand, clathrin-mediated vesicular trafficking, including clathrin heavy and light chains, and several clathrin adaptors, have been identified in the Atg5/Atg12 interactome [46], and earlier studies identified clathrin heavy chain as a direct interactor for GABARAP [47]. Additional work is required to clarify the exact interaction surfaces between the UBLs in the Atg12-Atg5 conjugate and partner proteins.…”
Section: Structural Overviewmentioning
confidence: 99%
“…This interaction was proposed to be mediated by AIM/LIR and stimulate Atg8 conjugation. On the other hand, clathrin-mediated vesicular trafficking, including clathrin heavy and light chains, and several clathrin adaptors, have been identified in the Atg5/Atg12 interactome [46], and earlier studies identified clathrin heavy chain as a direct interactor for GABARAP [47]. Additional work is required to clarify the exact interaction surfaces between the UBLs in the Atg12-Atg5 conjugate and partner proteins.…”
Section: Structural Overviewmentioning
confidence: 99%
“…In parallel, deficiency of the GABARAP-type subfamily may additionally directly disturb the intracellular distribution of surface proteins, especially those containing functional interaction motifs [ 52 ]. Interestingly, recent results from a yet unpublished study show altered surfaceome composition of Atg5 -/- mouse embryonic fibroblasts [ 57 ]. ATG5 is a key component of the LC3/GABARAP lipidation machinery which is essential for their integration into autophagy-related and unrelated membranes [ 53 ].…”
Section: Discussionmentioning
confidence: 99%